Comparative Study of the Use of FIFO and Average Inventory Accounting Methods in Manufacturing Companies - Rahmat Purnomo; Nita Priska Ambarita (Pt. Anagata Sembagi Education, 2025)
Inventory valuation and recording play a crucial role in shaping the quality of financial reporting, particularly in the manufacturing industry where production processes and inventory flow are complex. This study addresses how the use of different inventory accounting methods FIFO (First-In, First-Out) and Average (weighted average) impacts not only net income, but also inventory management efficiency and the company’s strategic positioning in the market. The objective of this research is to conduct a comparative analysis of the effects of these two methods within the accounting practices of manufacturing companies in Indonesia. A qualitative approach was employed through case studies of two large-scale manufacturing firms, using data collected from in-depth interviews and internal financial documentation. The results show that the FIFO method tends to generate higher net profits during periods of rising raw material prices, although it also leads to increased tax obligations. In contrast, the Average method offers more stable reporting outcomes and administrative efficiency, especially in businesses with homogeneous products and high inventory turnover. The discussion draws connections between these findings and PSAK 14, as well as prior literature, highlighting the importance of aligning inventory valuation methods with the operational context and strategic objectives of each company. Ultimately, the study concludes that no single method is universally superior. The effectiveness of implementation depends largely on business characteristics, the company’s internal recording system, and managerial priorities. These findings enhance theoretical understanding by framing inventory accounting choices as strategic financial decisions and offer practical insights for managers seeking to align financial reporting with long-term competitiveness.